Implementation of non-isolated three-port converter through augmented time response - Ramya Devasahayam; Godwin Immanuel D (Institute of Advanced Engineering and Science, 2021)
The work is concerning a multi-port dc-dc converter with improved time response and steady state output. Here the converter carries bare amount of switches for managing the power with mono inductance. The inductance and along with that the switched capacitance are pre owned to bring large voltage gain. This paper put forwarded an appropriate controller for the closed loop monitored high-gain converter with three ports. Higher is that the conversion rate. This converter is also a good interface between DC-source and load that aims to progressing time response with FLC and PI controller in the closed loop system. The converter with the PI controller and FLC is look over and the fast responses are compared with time domain specifications. The simulation outcome indicates that the FLC based converter brings most excellent time domain response.